The legend of Sigurd and Gudrun - Tolkien, J R R (HarperCollins, 2009)
Tolkien's version of the great legend of Northern antiquity. In the first part, we follow the adventures of Sigurd, the slayer of Fafnir, and his betrothal to the Valkyrie Brynhild. In the second, the tragedy mounts to its end in the murder of Sigurd at the hands of his blood-brothers, the suicide of Brynhild, and the despair of Gudrún.